2008
DOI: 10.2337/db08-0214
|View full text |Cite
|
Sign up to set email alerts
|

FTO Variants Are Associated With Obesity in the Chinese and Malay Populations in Singapore

Abstract: OBJECTIVE-Association between genetic variants at the FTO locus and obesity has been consistently observed in populations of European ancestry and inconsistently in non-Europeans. The aim of this study was to examine the effects of FTO variants on obesity and type 2 diabetes in Southeast Asian populations.RESEARCH DESIGN AND METHODS-We examined associations between nine previously reported FTO single nucleotide polymorphisms (SNPs) with obesity, type 2 diabetes, and related traits in 4,298 participants (2,919 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 26 publications
8
118
2
4
Order By: Relevance
“…7,8 Similar replication efforts involving other novel variants in diverse ethnic groups are necessary to corroborate initial findings from European studies and characterize their genetic contribution to obesity in other ethnicities. The aim of this study was to evaluate whether variants/loci identified in populations of European descent are important in Chinese, Malay and Indian ethnic groups, the three major ethnic groups in Asia.…”
Section: Introductionmentioning
confidence: 88%
“…7,8 Similar replication efforts involving other novel variants in diverse ethnic groups are necessary to corroborate initial findings from European studies and characterize their genetic contribution to obesity in other ethnicities. The aim of this study was to evaluate whether variants/loci identified in populations of European descent are important in Chinese, Malay and Indian ethnic groups, the three major ethnic groups in Asia.…”
Section: Introductionmentioning
confidence: 88%
“…7,8 A set of single-nucleotide polymorphisms (SNPs) in the first intron of FTO are strongly associated with adiposity/obesity and related phenotypes. [7][8][9][10][11][12][13][14][15][16][17] It has been shown that adults homozygous for the risk allele at rs9939609 weigh on average B3 kg more than those homozygous for the other allele. 7 FTO genotype has also been reported to be associated with adiposity in children [7][8][9] and the strength of its influence to increase during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…The full influence of FTO will only become clear through more thorough investigation of its interactions with environmental factors such as PA levels. Three studies have reported interactions between PA and FTO genotype in adults, with low activity levels being associated with enhanced genotype effects, [24][25][26] whereas other studies have reported no interaction with PA. 17,27 However, to the best of our knowledge, no such studies have been conducted in pre-adults. We report here the influence of rs17817449 on adiposity in two cohorts of children, with ages ranging from 1 to 18 years.…”
Section: Introductionmentioning
confidence: 99%
“…26 The SNP is reported to have a high minor allele frequency in Caucasians (∼0.4) but very low in Asian population (∼0.1), whereas its association with obesity and type II diabetes has been confirmed in many populations but not in Chinese Han subjects. 11,[18][19][20][21][22][23][24][25][26][34][35][36][37][38] The six GWAS SNPs were found to be associated with type II diabetes and have been replicated for Chinese and Japanese populations only for association with type II diabetes. [27][28][29] However, these SNPs have not been previously studied with respect to obesity, and the Pakistani population represents an interesting ethnic group because of the many cultural and social restrictions and with an increasing rate of obesity and type II diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The association of common FTO variants, especially rs9939609, with obesity has been confirmed in Caucasians; however, the results in Asian populations are conflicting. [16][17][18][19][20][21][22][23][24][25] In Pakistan, there is limited research in the field of obesity genetics. A recent study in the Pakistani population indicated the association of this SNP with obesity in women and proposed that the SNP may play its role by affecting plasma glucose and leptin levels.…”
Section: Introductionmentioning
confidence: 99%